1987
DOI: 10.1128/iai.55.10.2518-2525.1987
|View full text |Cite
|
Sign up to set email alerts
|

Hypochlorous acid-promoted loss of metabolic energy in Escherichia coli

Abstract: Oxidation of Escherichia coli by hypochlorous acid (HOCl) or chloramine (NH2Cl) gives rise to massive hydrolysis of cytosolic nucleotide phosphoanhydride bonds, although no immediate change occurs in either the nucleotide pool size or the concentrations of extracellular end products of AMP catabolism. Titrimetric curves of the extent of hydrolysis coincide with curves for loss of cell viability, e.g., reduction in the adenylate energy charge from 0.8 to 0.1-0.2 accompanies loss of 99% of the bacterial CFU. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0
2

Year Published

1990
1990
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 46 publications
2
35
0
2
Order By: Relevance
“…The majority of respiratory and transport processes are associated with cytoplasmic membranes in prokaryotes (Boos and Lucht 1996;Maloney and Wilson 1996). Chlorine-induced injury to this membrane and associated transport processes reduced membrane potential and respiratory activity and significantly reduced culturability (Albrich and Hurst 1982;Barrette et al 1987). Similar responses following disinfection were observed in this study, where the number of cells possessing a membrane potential (Rh123) and respiratory activity (CTC) decreased, while cells demonstrating a loss of membrane potential increased (DiBAC 4 (3)).…”
Section: Discussionsupporting
confidence: 72%
“…The majority of respiratory and transport processes are associated with cytoplasmic membranes in prokaryotes (Boos and Lucht 1996;Maloney and Wilson 1996). Chlorine-induced injury to this membrane and associated transport processes reduced membrane potential and respiratory activity and significantly reduced culturability (Albrich and Hurst 1982;Barrette et al 1987). Similar responses following disinfection were observed in this study, where the number of cells possessing a membrane potential (Rh123) and respiratory activity (CTC) decreased, while cells demonstrating a loss of membrane potential increased (DiBAC 4 (3)).…”
Section: Discussionsupporting
confidence: 72%
“…The fact that some cells can still be grown on agar plates demonstrates that this level of chlorine represents a sublethal concentration and as such does not cause any damage to the membrane integrity since no cells take up PI. The loss of cultivability when cells are exposed to stress conditions (such as extreme temperatures, nutrient starvation, or chlorine oxidative stress exposure) is an effect which can be explained by injury to the cytoplasmic membrane and transport processes which reduce the membrane potential and respiratory activity and, consequently, cultivability [1,3,18]. However, Yamamoto et al [37] have already demonstrated that, even after losing cultivability due to nutrient starvation, cells retain intact DNA and RNA and, in favorable conditions, can recover, elongate, and multiply.…”
Section: Discussionmentioning
confidence: 99%
“…Among the chemical sites susceptible to oxidation are sulfhydryl groups, iron-sulfur centers, sulfur-either groups, unsaturated fatty acids, as well as many others. Reported early effects are the loss of membrane transport function (49), disruption of the membrane electron transport chain (50), dissipation of adenylate energy reserves (51), and suppression of DNA synthesis through disruption of the interaction of the cell membrane with the chromosomal origin of replication (52).…”
mentioning
confidence: 99%